Neopuccinia (Pucciniales): a new Puccinia-like genus from the Brazilian Cerrado - Martins Junior, Alcindo S.; Sakuragui, Cássia M.; Hennen, Joe F.; Carvalho Junior, Aníbal A. (Phytotaxa, 2019)
Neopuccinia, a new Pucciniales genus, based on N. bursa found on Protium heptaphyllum (Burseraceae) in the Brazilian Cerrado, is described and illustrated. The combined phylogenetic analyses of molecular data from nuc rDNA 18S and 28S markers demonstrate that the new taxon is an independent lineage and thus a taxonomically distinct unit. It is morphologically characterized by bag-like projections arising from the bicellular teliospore wall, like those found in Puccinia.